Screening and identification of nucleocapsid protein-nanobodies that inhibited Newcastle disease virus replication in DF-1 cells - Fan, Wenqi; Ji, Pinpin; Sun, Xuwen; Kong, Min; Zhou, Ning; Zhang, Qiang; Wang, Ying; Liu, Qianqian; Li, Xiaoxuan; Zhou, En-Min; Zhao, Qin; Sun, Yani (Frontiers in Microbiology, 2022)
Newcastle disease (ND) is an acute and highly contagious infectious disease found in poultry. Although commercial ND virus (NDV) vaccines are universally used, some case reports persistently documented vaccination failure. Therefore, novel strategies are still required to control the occurrence of the disease in chickens. Recently, nanobodies (Nbs), which have the advantages of small molecular weight and low production costs, have been shown to be promising therapeutics against viral infection. In the present study, a total of 16 Nbs against NDV nucleocapsid protein (NP) were screened from two libraries against NDV using phage display technology. Of the 16 screened Nbs, eight were prevented from binding to NDV NP protein through administering positive chicken sera for anti-NDV antibodies, indicating that the epitopes recognized by these eight Nbs were able to induce the immune response after the chickens were challenged with NDV stock. Subsequently, transfection assay, construction of recombinant DF-1 cells capable of expressing different nanobodies and viral inhibition assay were used to screen the nanobodies inhibiting NDV replication. The results demonstrated that Nb18, Nb30 and Nb88 significantly inhibited the replication of Class I and different genotypes of Class II NDV strains in DF-1 cells when they were expressed in the cytoplasm. Collectively, these nanobodies provided some new tools for researching the functions of NDV NP protein and may be as a novel strategy for designing drugs against NDV infection in chickens.